2015
DOI: 10.1021/jp5107058
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Fate of Methyl Vinyl Ketone: Peroxy Radical Reactions with NO and HO2

Abstract: First generation product yields from the OHinitiated oxidation of methyl vinyl ketone (3-buten-2-one, MVK) under both low and high NO conditions are reported. In the low NO chemistry, three distinct reaction channels are identified leading to the formation of (1) OH, glycolaldehyde, and acetyl peroxy R2a, (2) a hydroperoxide R2b, and (3) an α-diketone R2c. The α-diketone likely results from HO x -neutral chemistry previously only known to occur in reactions of HO 2 with halogenated peroxy radicals. Quantum che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
157
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(177 citation statements)
references
References 59 publications
18
157
0
Order By: Relevance
“…This mechanism is based on Mao et al (2013b), but has been significantly revised to incorporate recent laboratory updates on isoprene oxidation by OH, ozone, and NO 3 (Schwantes et al, 2015;Bates et al, 2014Bates et al, , 2016St. Clair et al, 2016;Praske et al, 2015;Müller et al, 2014;Lee et al, 2014;Crounse et al, 2011). One major feature is the suppression of the δ-isoprene hydroxy peroxy radical (δ-ISOPO 2 ) and subsequent reaction pathways in the model, as these channels are considered to be of minor importance under ambient conditions Bates et al, 2014).…”
Section: Am3 Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism is based on Mao et al (2013b), but has been significantly revised to incorporate recent laboratory updates on isoprene oxidation by OH, ozone, and NO 3 (Schwantes et al, 2015;Bates et al, 2014Bates et al, , 2016St. Clair et al, 2016;Praske et al, 2015;Müller et al, 2014;Lee et al, 2014;Crounse et al, 2011). One major feature is the suppression of the δ-isoprene hydroxy peroxy radical (δ-ISOPO 2 ) and subsequent reaction pathways in the model, as these channels are considered to be of minor importance under ambient conditions Bates et al, 2014).…”
Section: Am3 Modelmentioning
confidence: 99%
“…The treatment of β-and δ-ISOPO 2 will not only affect the speciation of organic nitrates but also the production of ozone due to different NO x recycling efficiency in their secondary products. We also include updated chemistry for methylvinyl ketone (MVK; Praske et al, 2015), an updated yield of hydroxy hydroperoxides (ISOPOOH; Bates et al, 2016;St. Clair et al, 2016), fast photolysis of carbonyl organic nitrates , and an updated ozonolysis rate of ISOPNB .…”
Section: Am3 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…So, for measured OH to be greater than modeled OH, there must be unknown OH sources, which could be either primary sources, such as photolysis of an unknown chemical species, or secondary sources, such as recycling of HO x to OH within the BVOC oxidation mechanisms. These discrepancies and the speculation about OH recycling have led to increased interest in the detailed chemical oxidation mechanisms for these BVOCs, particularly isoprene (Paulot et al 2009;Peeters et al 2009;Peeters and Müller 2010;Crounse et al 2011Crounse et al , 2012Crounse et al , 2013Praske et al 2015;St. Clair et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This was shown for the acetylperoxy radical with an OH yield of 50 % Winiberg et al, 2016). In a recent study by Praske et al (2015), product yields from the reaction of MVK derived peroxy radicals with HO 2 were investigated. Similar to the acetylperoxy radical, product yields demonstrated that only one third of the reaction yields hydroxyperoxides and that two additional reaction channels exist, both of which could lead to the reformation of OH.…”
Section: Introductionmentioning
confidence: 92%